REKSADANA SYARIAH SEBAGAI INSTRUMEN INVESTASI HALAL DALAM PERKEMBANGAN PASAR MODAL SYARIAH DI INDONESIA - Atika Dwi Yuda Sakinah (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
Sharia mutual funds are a form of collective investment in which public funds are managed by professionals while adhering to Islamic sharia principles. These instruments are not only profit-oriented but also emphasize halal (permissible) compliance, fairness, and transparency in fund management. This article aims to examine the concept of sharia mutual funds, their legal basis, management mechanisms, and their development and prospects in the Indonesian sharia capital market. This study uses a desk research approach and analyzes various literature, regulations from the Financial Services Authority (OJK), and fatwas issued by the National Sharia Council of the Indonesian Ulema Council (MUI). The results indicate that sharia mutual funds have a strong legal basis and management mechanisms, and comply with Islamic sharia principles, including the process of screening and eliminating non-halal elements. However, the development of sharia mutual funds in Indonesia still faces challenges, particularly related to the low level of sharia financial literacy in the community. Therefore, ongoing education and outreach efforts are needed to increase public interest and understanding of sharia mutual fund investments. Keywords: sharia mutual funds, sharia capital market, halal investment, sharia principles